Pandangan Gen Z: Customer Review Dan Customer Rating Terhadap Keputusan Pembelian Produk Di Marketplace Tokopedia - Latifa, Havna Nur; Hidayat, Syamsul; Dwihandoko, Toto Heru (CV. ULIL ALBAB CORP, 2025)
This study examines Gen Z’s perspective on the influence of Customer Reviews and Customer Ratings on purchase decisions in the Tokopedia marketplace. Customer Reviews are consumer feedback based on product or service usage experiences, while Customer Ratings are evaluations using a scale, typically represented by stars. Purchase decisions refer to the process of selecting a product after identifying needs, gathering information, and comparing alternatives. Employing a quantitative paradigm in conjunction with multiple linear regression analysis, this inquiry was oriented toward members of Generation Z residing within Mojokerto Regency, aged 17 to 28 years, who possessed both purchasing capacity and registered Tokopedia accounts. The selection of participants was executed through a purposive sampling technique, culminating in the acquisition of 100 valid respondents., and data were collected via questionnaires. The t-test results revealed that both Customer Reviews and Customer Ratings exert a constructive and consequential influence upon purchasing determinations, as evidenced by a probability value inferior to 0.05. The Adjusted R² value of 0.598 indicates that 59.8% of purchase decision variation is explained by these two variables, Whilst 40.2% is governed by heterogeneous contingencies external to the model’s explanatory domain. These findings highlight the crucial role of online reviews and ratings in shaping Gen Z consumers’ purchasing behavior.